(untitled) (Journal of the College of Languages (JCL), 2019)
The paper tackles two topics. The first is about the term "Ремейк" which is very common in contemporary Russian literature; it has counterparts such as " Обработка" and " Переделка", where these two may indicate any of the following meanings (remake, reformulate, rewrite, treatment, modification, change). It has been shown that this term does not have a stable definition. Also, the role of this term in literary studies has been mentioned along with how it has come to its peak of use in post-modern literature. The second is that I have taken a sample of well-known works in Russian literature " On the Eve, On the Eve " by the contemporary Russian writer YevgueniBobov, and shown the effort of the writer in re-thinking about the novel "On the Eve" by the classical Russian writer Ivan Turgenev. The main theme in both is love towards Russia, and I have shown that the common factor in both is the unchanged names of the characters. At the same time, the satirical parody is not seen as the dominating theme in the text; it is a principal basis in the organizing the text as to the structure of the them and of the character. It is seen as an essential element in the artistic world of the novel, which is built within post-modernity. Moreover, the meaning therein, is not dependent extensively upon parody, for it changes narration to a repeated artistic style. Аннотация В статье рассматривается слово «Ремейк», термин который, широко используемый в современной русской литературе. Ремейк является синонимом «Обработка» и «Переделка». Несмотря на то, что «Ремейк» не имеет устойчивого определения, но тут была указана роль этого термина, и его функционирование в постмодернистской русской литературе. Это во-первых. Во-вторых, для того, чтобы показать усилия автора переосмыслить роман « Накануне » классического русского писателя Ивана Тургенева, мы взяли для этого образец знаменитого произведения в русской литературе современного русского писателя Евгений Попов «Накануне, Накануне ». Как известно, что тема любви к России и неизменных персонажей героев- как общий фактор, доминируют в обоих романах. При это, сатирическая пародия не воспринимается в качестве доминирующей темы в тексте; а она будет главным фактором для образования текста относительно структуры его. Она замечена как существенный элемент в художественном мире романа, который построен в рамках постмодернизма. Более того, семантические значение текста не зависит в значительной степени от пародии, поскольку оно меняет повествование на повторяющийся художественный стиль.